The Role of Brand Image and Product Quality on Purchase Intention (Study Literature Review) - Niu Haitao (Dinasti International Journal of Management Science, 2022)
The literature review article on the Role of Brand Image and Product Quality on Purchase Intention (Study Literature Review) is a scientific article that aims to build a research hypothesis on the influence of variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Brand Image has an effect on Purchase Intention; and 2) Product Quality has an effect on Purchase Intention. Apart from these 3 exogenous variables that affect the endogenous variable of Purchase Intention, there are still many other factors including Price, Place and Service Quality variables.